Ceramic nanocomposite membranes and membrane fouling: A review. (15th May 2020) - Li, Chen; Sun, Wenjun; Lu, Zedong; Ao, Xiuwei; Li, Simiao
Abstract: Membrane technologies have broad applications in the removal of contaminants from drinking water and wastewater. In recent decades, ceramic membrane has made rapid progress in industrial/municipal wastewater treatment and drinking water treatment owing to their advantageous properties over conventional polymeric membrane. The beneficial characteristics of ceramic membranes include fouling resistance, high permeability, good recoverability, chemical stability, and long life time, which have found applications with the recent innovations in both fabrication methods and nanotechnology. Therefore, ceramic membranes hold great promise for potential applications in water treatment. This paper mainly reviews the progress in the research and development of ceramic membranes, with key focus on porous ceramic membranes and nanomaterial-functionalized ceramic membranes for nanofiltration or catalysis. The current state of the available ceramic membranes in industry and academia, and their potential advantages, limitations and applications are reviewed. The last section of the review focuses on ceramic membrane fouling and the efforts towards ceramic membrane fouling mitigation. The advances in ceramic membrane technologies have rarely been widely reviewed before, therefore, this review could be served as a guide for the new entrants to the field, as well to the established researchers. Graphical abstract: Image 1 Highlights: Review covers current state-of-the-art of ceramic membranes. Ceramic membranes hold great promise for applications in water treatment. Nanotechnology-based ceramic membranes and catalytic membranes are reviewed. Membrane fouling, with implications and mitigation strategies are reviewed. Applications of ceramic membrane technology and future directions are discussed.